Aislamiento e identificación de bacterias termorresistentes en conservas enlatadas de Bactris gasipaes “palmito” de la empresa Caynarachi S.A., Trujillo-Perú - BENITES CAIGUARAICO, Sandy Mayerling (2019)
The objective of this research was to isolate and identify heat-resistant bacteria from canned canned Bactris gasipaes "palmito" from Caynarachi S.A. From a batch of 265 units, 8 preserves with signs of bulging were selected, according to the Peruvian Technical Standard ISO 2859-1. Selected canned samples were incubated for 10 days at 55 ° C. For enrichment, 1 g of crushed heart of each sample was placed in duplicate in 9 ml of BHI broth at a temperature of 55 ° C for 48 h, where microorganisms were obtained in aerobic and anaerobic conditions due to the presence of turbidity. For the isolation, serial dilutions of 10-1 to 10-4 were made and 0.1 ml of the last two dilutions in BHI and PCA agar were seeded, which were incubated to the same initial conditions (aerobic and anaerobic). The macroscopic and microscopic characteristics of the isolated colonies were observed, by means of Gram stain, Wirtz stain for spores and identified by biochemical tests. When evaluating biochemical behavior, tests indicated positive catalase, positive gelatinase, glucose fermentation, sucrose, lactose, with gas production, positive nitrate reduction, negative citrate and negative phenylalanine. We managed to isolate and identify 8 heat-resistant bacterial cultures with growth at 55 ° C corresponding to the genus Bacillus, all Gram positive, from colonies with irregular edges, ground glass appearance, gas producers and with aerobic and anaerobic growth in the samples of "palmito" canned used.